Using computed tomography angiography and computational fluid dynamics to study aortic coarctation in different arch morphologies - Qin, Jinjie; Ouyang, Da; Yan, Taocui; Wang, Haoru; Guo, Kui; Jin, Xin; Pan, Zhengxia; He, Ling (Frontiers in Pediatrics, 2023)
Objective: To study the differences in computed tomography angiography (CTA) imaging of gothic arches, crenel arches and romanesque arches in children with Aortic Coarctation (CoA), and to apply computational fluid dynamics (CFD) to study hemodynamic changes in CoA children with gothic arch aorta. Methods: The case data and CTA data of children diagnosed with CoA (95 cases) in our hospital were retrospectively collected, and the morphology of the aortic arch in the children was defined as gothic arch (n=27), crenel arch (n=25) and romanesque arch (n=43). The three groups were compared with D1/AOA, D2/AOA, D3/AOA, D4/AOA, D5/AOA, and AAO-DAO angle, TAO-DAO angle, aortic arch height to width ratio (A/T). Computational fluid dynamics was applied to assess hemodynamic changes in children with gothic arches. Result: There were no significant differences about D1/AOA and D2/AOA among gothic arch, crenel arch and romanesque arch (P>0.05). The differences about D3/AOA, D4/AOA and D5/AOA among the three groups were statistically significant (P<0.05), D4/AOA, D5/AOA of the gothic arch group were smaller than the crenel arch group, and the D3/AOA and D5/AOA of gothic arch group were smaller than the romanesque arch group (P<0.05). The difference in AAO-DAO angle among the three groups was statistically significant (P<0.05), and the AAO-DAO angle of gothic arch was smaller than that of romanesque arch and crenel arch group (P<0.05). There was no significant difference in TAO-DAO angle between the three groups (P>0.05). The difference in A/T values among the three groups was statistically significant (P<0.05), and the A/T values: gothic arch> romanesque arch> crenel arch(P<0.05). The CFD calculation of children with gothic arch showed that the pressure drop between the distal stenosis and the descending aorta was 58 mmHg, and the flow rate at the isthmus and descending aorta was high and turbulent. Conclusion: Gothic aortic arch is common in CoA, it may put adverse effects on the development of the aortic isthmus and descending aorta, and its A/T value and AAO-DAO angle are high. CFD could assess hemodynamic changes in CoA. Keywords Aortic Coarctation (CoA); gothic arch; Computational Fluid Dynamics (CFD); AAO-DAO angle; computed tomography angiography (CTA)